Analisis Beban Kerja Unit Kerja Markas dan Satuan Pengawas Internal Palang Merah Indonesia DKI Jakarta (Jurnal Manajemen dan Organisasi, 2017)
Indonesian Red Cross (PMI) province of DKI Jakarta, Indonesia as the social organization is required to always be ready to meet all the needs of society. However, there are some problems in its implementation, such as fundraising target that has not been achieved, there is no Standard Operating Procedure (SOP), and there are some jobs that have not been implemented. Hence, workload analysis is required to determine the composition of the right amount of employees. The purposes of this study are: 1) Describing the business process on PMI’s Internal Headquarter Unit and Observer Squad; 2) Composing more accurately job descriptions; 3) Analyzing more efficiently and more effectively the workloads on the Internal Headquarter Unit and Observer Squad; and 4) Giving recommendation about the ideal employee numbers on the Internal Headquarter Unit and Observer Squad. The processing data method which used in this study was Full Time Equivalent (FTE). The result of workload analysis shows that new recruitment is not necessary, but downsizing in storage and pantry staff in general affairs should be conducted.